Acute toxicity and bioaccumulation of heavy metals in red tilapia fish - Aldoghachi, M.A.J.; Rahman, M.M.; Yusoff, Ismail; Sofian-Azirun, Mohd (Pakistan Agricultural Scientists Forum, 2016)
Juvenile hybrid tilapia (Oreochromis sp.) was tested with different concentration of heavy metals under varying exposure time to examine acute toxicity effect on their survival rate and bioaccumulation in fish tissues. Copper (Cu), cadmium (Cd) and zinc (Zn) was used at rates 0.0, 0.50, 1.0, 3.0 and 5.0 mg L-1. The medial lethal concentration of Cu, Cd and Zn (96h LC50) was determined to be 0.45, 0.7 and 2.1 mgL-1, respectively in a Probit transformed concentration - response curves. Fish tissues were digested in Nitric acid (65%) and Hydrogen pe roxide (35%) under microwave oven and analyzed by inductive coupled plasma optical emission spectrometry (ICP-OES, Model Perkin Elmer Optima 5300DV, USA). Tilapia fish mortality was significantly higher with higher concentration of toxic metals. The fish toxicity by heavy metals was in the following order: Cu > Cd > Zn. The liver tissues obtained the highest accumulation of Zn (423 mg kg-1) followed by Cu (136 mg kg-1) with the highest concentration of each toxic metal. The gill tissues recorded the highest accumulation of Cd (121.0 mg kg-1) with the highest concentration of Cd while muscle tissues accumulated the highest Zn concentration (31.0 mg kg-1) with the highest concentration of Zn. Accumulation of heavy metals in fish tissues of different organs was in the following order: liver > gills > muscles for Cu and Zn while gills > liver > muscles for Cd. Regardless of tissue organs accumulation of toxic metals increased with higher concentrations of heavy metals and exposure period.